The Analysis of Stunting Incidence Factors in Toddlers Aged 23-59 Months in the Work Area of the Padang Tiji Community Health Center, Pidie Regency, 2020 - Andika, Fauziah (International Journal of Science, Technology & Management, 2021)
Aceh is ranked third nationally for child stunting, behind East Nusa Tenggara (NTT) and West Sulawesi (Sulbar). Currently, he explained, the government is aggressively campaigning for the prevention and handling of stunting. This is because the prevalence of stunting for infants under five years of age (toddlers) in Indonesia in 2018 was 30.8%. Based on a report from Puskesmas Padang Tiji in 2018, there were 114 (18.4%) toddlers aged 23-59 months who experienced stunting, while in 2019 it increased to 138 (20.9%) toddlers with stunting. The purpose of this study was to analyze the incidence of stunting in children aged 23-59 months in the Padangtiji Community Health Center in 2020. This research method uses a case control approach. In the study, the control samples were toddlers who came to Posyandu who were randomly selected. The research sample was 50 cases and 50 controls, namely 1: 1. This research was conducted on December 10, 2020 to December 21, 2020. The statistical test used is the chi-square test by looking at the OR value and data analysis using univariate and bivariate analysis. The results of this study were the relationship between the incidence of stunting with exclusive breastfeeding (P = 0.016) (OR = 3.071), birth weight (P = 0.678), infectious diseases (P = 0.523) and birth spacing (P = 0.043) (OR = 2,421). The conclusion of this study is that there is a relationship between exclusive breastfeeding and birth spacing with the incidence of stunting in toddlers aged 23-59 months in the working area of Puskesmas Padang Tiji in 2020. The suggestions are expected to further improve health promotion in the form of counseling related to the causes and prevention of stunting in order to increase knowledge mothers regarding stunting and prevention related to infectious diseases in reducing morbidity that can lead to stunting.